Comparing frontal eye field and superior colliculus contributions to covert spatial attention - Anil Bollimunta (Nature Portfolio, 2018)
Superior colliculus (SC) and frontal eye fields (FEF) contain visuo-motor maps but their contributions to selective attention are not fully understood. Here, the authors perform reversible inactivations of the SC or FEF and report that loss of SC activity has a more devastating effect on attention.